Acetylated starch of ofada rice as a sustained release polymer in microsphere formulations of repaglinide (2015)
Background: Acetylated starches with degrees of substitution (DS) of > 2 have been found suitable for sustained release applications because of their hydrophobic nature and thermoplasticity. The short half-life and high dosing frequency of repaglinide make it an ideal candidate for sustained release. Objectives: To formulate and evaluate repaglinide microspheres using acetylated starch of the indigenous rice species Oryza glaberrima Steud (Ofada) as polymer. Materials and Methods: Ofada rice starch was acetylated with acetic anhydride in pyridine (DS 2.68) and characterized for morphology (Scanning electron microscope, SEM), Crystallinity (Fourier Transform Infra-Red spectroscopy, FTIR, and X-ray diffraction crystallography, XRD), density and swelling. Microspheres of repaglinide were prepared by emulsification solvent-evaporation method, varying the drug-polymer ratio (1:2, 1:4, 1:8 and 1:10) and polymer type (ethyl cellulose as standard). Microspheres were characterized for particle size, wall thickness, swelling, entrapment efficiency, time taken for 80% drug release (t80) and permeability. Data obtained from in-vitro drug release studies were fitted to various kinetic models. Results: Repaglinide microspheres were near spherical, discrete and of size range 23.45 ± 4.25 to 44.55±3.85 μm. FTIR spectra revealed the absence of drug–polymer interaction and complete drug entrapment. Particle size, swelling, entrapment and wall thickness increased with drug: polymer ratio and were generally higher in microspheres containing acetylated Ofada rice starch while t80 (195±6.60 - 395± 24.75 min) was lower. Drug release fitted the Hixson-Crowell kinetic model. Conclusions: The acetylated starch of Ofada rice was found suitable as a polymer to sustain the release of repaglinide in microsphere formulations.